Responsible research and innovation training programs: implementation and evaluation of the HEIRRI project - Ružica Tokalić; Ivan Buljan; Niels Mejlgaard; Mar Carrió; Alexander Lang; Gema Revuelta; Ana Marušić; HEIRRI Consortium (Oxford University Press, 2021)
Responsible research and innovation, or RRI, is a concept that aims to bring together society and science for a better future. There are six key elements of RRI: public engagement, gender equality, science education, open access, ethics and governance. Higher Education Institutions and Responsible Research and Innovation (HEIRRI) project aimed to bring the concept of RRI into the educational system. Using state-of-the-art review of good practices, HEIRRI team developed 10 training programs on RRI for different higher education institution educational levels, including a summer school and a massive open online course (MOOC). We conducted pilot of the trainings and evaluated participants' experiences. Satisfaction with HEIRRI training programs on responsible research and innovation was high, both for participants and for the trainers, and trainings raised awareness of RRI. Participants' feedback was used to identify areas that need improvement and provided for recommendations for final versions of the HEIRRI training programs. In order to equip researchers with skills to recognize and apply RRI values, RRI should be included in their education. HEIRRI training is suitable for a range of different disciplines, including forensic science, and is free to use and adjust for specific contexts (available from: https://rri-tools.eu/heirri-training-programmes). Supplemental data for this article is available online at https://doi.org/10.1080/20961790.2021.1970319 .